2018
DOI: 10.4236/oalib.1104364
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Animal-Assisted Intervention on Physiological Measures of Stress and Anxiety in Graduate Professional Physical Therapy Students

Abstract: Introduction. Graduate professional educational programs are very rigorous and challenging, often leading to increased physiological stress and perceived anxiety for the enrolled student. Stress and anxiety levels in physical therapy students are higher than that in their age and gender matched peers. The purpose of this study was to assess the impact of an animal-assisted intervention on stress and anxiety of entry-level physical therapist (PT) students prior to a laboratory practical exam. Subjects. Twenty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Nevertheless, an effect on students’ physical well-being did not occur in this study. The influence dogs have on students’ physical well-being cannot be unambiguously answered, as some studies have linked DAI in higher education to improvements in health factors such as lower blood pressure and cortisol levels [ 32 , 42 , 43 , 81 ], while other studies have failed to confirm such effects [ 29 , 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an effect on students’ physical well-being did not occur in this study. The influence dogs have on students’ physical well-being cannot be unambiguously answered, as some studies have linked DAI in higher education to improvements in health factors such as lower blood pressure and cortisol levels [ 32 , 42 , 43 , 81 ], while other studies have failed to confirm such effects [ 29 , 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although providing this kind of intervention to college and university students is a fairly new undertaking [ 26 ], there is promising evidence that AAIs can, amongst others, result in higher ratings of momentary positive emotions, a reduction in stress-related negative emotions [ 27 , 28 ], psychological and physical markers of stress [ 29 , 30 , 31 , 32 ], anxiety [ 33 , 34 , 35 , 36 ], and homesickness while increasing their satisfaction with life, connectedness to campus [ 37 , 38 ], behavioral aspects of academic success [ 39 ], well-being and improving their social skills as well as their mood [ 29 , 33 , 40 ]. Furthermore, Daltry and Mehr [ 41 ] found that having animals on campus may promote the services offered by student counseling centers on campus, as a lot of students were unaware of them before implementing the AAI.…”
Section: Introductionmentioning
confidence: 99%
“…Trammell [197] wrong outcomes Turner et al [198] wrong study design Voelpel et al [199] wrong study design Walsh [200] wrong study design Wheeler et al [201] wrong intervention Williams et al [202] wrong outcomes…”
Section: References Of Excluded Studies From Full Manuscript Search Reason Excludedmentioning
confidence: 99%